DNA Barcode as an effective tool in the identification of billfishes (Scombroidei, Teleostei) from exported specimens - Rodrigues, Carlos E. [UNESP]; de Carvalho, Daniel Eduardo Visciano; Garcia, Yasmin [UNESP]; Hashimoto, Diogo T. [UNESP]; Foresti, Fausto [UNESP]; Porto-Foresti, Fábio [UNESP] (Elsevier, 2021)
DNA Barcode were used to identify species Billfishes and swordfish Xiphias gladius appeared as the only billfish species exported in Brazil. This system has been used successfully in the identification of species and samples not characterized, or illegally traded, as well as products from threatened species. The DNA barcode technique was used in the identification of billfish products exported through the terminal of the International Airport of São Paulo. Samples of billfish tissues were collected during the procedures to export the products to the United States and England. DNA sequencing permitted to certify that 100 % of the sampled products inspected were correctly identified as Xiphias gladius, thus confirming the NCM information about the species declared by the exporter. The high index of similarity of the sequences obtained in the samples with the sequences deposited in the Bold Systems and GenBank which is an NCBI platform (National Center for Biotechnology Information) platform for this species allow the validation and adequacy of the technique used, with direct application mainly in the process of inspection of the commercialization and exportation of fishery products.
Keywords: COI; Commerce; DNA Barcode; Fisheries; Species identification; Xiphias gladius